Implementation evaluation of mhealth interventions in the secondary prevention of coronary artery disease: a supplementary review. (25th January 2023) - Lynch, C; Braver, J; Issaka, A; De Moel-Mandel, C; Zisis, G; Carrington, M; Oldenburg, B
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): La Trobe University Introduction: mHealth technologies have evolved rapidly in recent years and are now widely implemented for the secondary prevention of coronary artery disease (CAD). While there is increasing evidence of their effectiveness, there are significant knowledge gaps concerning their reach, adoption, implementation, and maintenance. Purpose: This study evaluates internal and external validity dimensions of mHealth-enabled cardiac disease management programs (DMPs) using elements of Glasgow's RE-AIM (Reach-Effectiveness-Adoption-Implementation-Maintenance) Framework. It is a supplementary review to a systematic review and meta-analysis which evaluated effectiveness. Methods: From the 27 studies reviewed for the previous systematic review on effectiveness, a citation search was performed to identify additional publications reporting on elements of reach, adoption, implementation, and maintenance. All eligible publications were independently coded by two team members using the 23-item RE-AIM extraction tool and analysed using mixed-methods to ascertain the reporting of these elements. Results: In total, 35 publications were included in the analysis, 27 from the previous systematic review and 8 supplementary publications. The items for the Reach dimension indicated participant participation rates ranging between 18% to 67%, and used a wide range of exclusion criteria, relating to mental and cognitive impairment (37%), physical impairments (41%) and language issues (26%). Most (44%) interventions were solely home-based with nurses being the main health professionals delivering the intervention (adoption items). The implementation and maintenance items showed intervention duration of between 4-52 weeks (median 24 weeks) with intervention follow-up of between 1-48 months (median 6 months). Conclusions: This review found great heterogeneity in the duration and follow-up of mHealth-enabled DMPs for patients with CAD, with low participation rates suggesting access barriers. Addressing RE-AIM dimensions in the evaluation of mHealth-enabled cardiac DMPs for patients with CAD is critically important for identifying factors affecting the reach, adoption, implementation, and maintenance of interventions in order to improve translation of research evidence into practice for patients, clinicians and health service organisations.